Study of Magnetic Flux and Shear Stress of OEM Damper featuring MR Fluid - Muhamad, P.; Unuh, M. H.; Norfazrina, H. M. Y.; Ismail, M. A.; Tanasta, Z. (Journal of Advanced Research in Applied Mechanics, 2020)
The applications of semi-active damper employing magnetorheological (MR) fluids keep increasing in fulfilling the demand to control undesired vibration effect. The aim of this study is to evaluate that the new design OEM damper can yield necessary magnetic flux and shear stress. In this study, a finite element model was built to analyse and examine the new design of OEM damper. The results show that the new design OEM damper can generate the necessary magnetic flux density to react with superior properties of MR fluid. The nodal solution illustrates the saturation of magnetic flux density. The magnetic flux density is directly proportional to applied current. The simulation results also verified the induced magnetic field can manifest the shear stress development in the MR fluid.